Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.redox.2019.101363
|View full text |Cite
|
Sign up to set email alerts
|

Impaired inflammasome activation and bacterial clearance in G6PD deficiency due to defective NOX/p38 MAPK/AP-1 redox signaling

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) is the rate-limiting enzyme of the pentose phosphate pathway that modulates cellular redox homeostasis via the regeneration of NADPH. G6PD-deficient cells have a reduced ability to induce the innate immune response, thus increasing host susceptibility to pathogen infections. An important part of the immune response is the activation of the inflammasome. G6PD-deficient peripheral blood mononuclear cells (PBMCs) from patients and human monocytic (THP-1) cells were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…There is now accumulating evidence that G6PD de ciency affects cells other than erythrocytes 10,[21][22][23][24] . The replication and spread of respiratory viruses normally involves activation of the antiviral innate immune responses and culminates in the production of type I interferons (IFNs) and proin ammatory cytokines such as tumor necrosis factor-alpha (TNF-α), which in turn upregulate antiviral proteins 24 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is now accumulating evidence that G6PD de ciency affects cells other than erythrocytes 10,[21][22][23][24] . The replication and spread of respiratory viruses normally involves activation of the antiviral innate immune responses and culminates in the production of type I interferons (IFNs) and proin ammatory cytokines such as tumor necrosis factor-alpha (TNF-α), which in turn upregulate antiviral proteins 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, G6PD-de cient peripheral blood mononuclear cells (PBMCs) from patients and human monocytic (THP-1) cells showed impaired in ammasome activation. In particular, G6PD knockdown reduced the expression of mature interleukin (IL)-1β but not the expression of caspase-1 or the components of the in ammasome (NLRP3, ASC, and pro-Caspase-1) pathway 10 . Additionally, there was a differential expression of cytokines between the G6PD-de cient cells and the normal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 It has been regarded that p38 can activate MAPK to promote the cancer development and progression. [33][34][35] In addition, previous studies have confirmed the association between KLF4 and MAPK/p38 signaling. 36,37 Our study further verified the relation between KLF4 and MAPK/p38, suggesting that KLF4 could at as a key modulator on MAPK/ p38 signaling.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, the inflammasome activation is tightly regulated by a number of factors at the transcriptional level [ 31 ]. In addition to NF-κB activation, interferon regulatory factor 1 (IRF1), AP-1, and other transcriptional factors are involved in the transcriptional regulation of the components of NLRP3 inflammasome assembly [ 31 , 34 , 35 ]. These priming signals also induce post-translational modifications for several inflammasome components, i.e., NLRP3 deubiquitination and the ubiquitination and phosphorylation of ASC, for further activation of inflammasome complex assembly [ 36 ].…”
Section: Overview Of Inflammasomesmentioning
confidence: 99%